MO608: INV-202, A CB1 Receptor Blocker, Reduces Renal Injury in A Murine Model of Streptozotocin (STZ)-Induced Type-1 Diabetes. (3rd May 2022) - Jourdan, Tony; Jacquot, Laetitia; Degrace, Pascal; Verges, Bruno; Crater, Glenn
Abstract: BACKGROUND AND AIMS: Renal diseases remain a burden for Public Health and chronic kidney disease (CKD) affects several millions of individuals worldwide. Diabetic Nephropathy (DN) is the most frequent consequence of diabetes and is characterized by an increase in urinary albumin excretion and progressive loss of renal function associated with glomerular basement membrane thickening, mesangial expansion, nodular glomerular sclerosis and tubulointerstitial fibrosis. To date, there are few treatments that can prevent its progression. Indeed, current therapeutic approaches including RAAS blockers, SGLT2 inhibitors or both approaches combined do not fully abrogate DN progression. A growing body of experimental evidence suggests that modulation of the endocannabinoid system, and in particular its type 1 receptor (CB1R), may be a therapeutic tool in the management of CKD and more particularly DN. CB1R blockade represents a potential therapeutic modality in the fight against obesity, diabetes and their metabolic sequelae. In kidney, CB1R inhibition promotes a reduction in albuminuria, renal fibrosis and preserves renal function in both obesity-induced and diabetic nephropathy in mice mainly through a direct action of CB1R in podocytes and/or proximal tubules. INV-202 is a peripherally acting Cannabinoid receptor-1 (CB1r) inverse agonist that is under clinical development for the treatment of diseases associated with diabetes and metabolic syndrome. Here we report the effects of INV-202 on renal function and associated parameters in a preclinical model of diabetic nephropathy. METHOD: Twelve weeks after the initiation of diabetes using streptozotocin, C57BL6/J mice (8 per treatment group) were randomized to receive a daily oral dose of INV-202, 0.3 mg/kg and 3 mg/kg or vehicle for 4 weeks. Five mice not treated with STZ were used as a nondiabetic control. At the end of treatment, animals were sacrificed. Urinary albumin-to-creatinine ratio (ACR), renal matrix remodelling, glomerular filtration and interstitial fibrosis were assessed in addition to glucose levels, body weight and organ weights. RESULTS: After 28 days of treatment, there was no significant effect on hyperglycemia or body weight with either dose of INV-202. Renal and hepatic weights were reduced while heart weight was unaffected. This remained true when normalizing for tibial length. Compared with vehicle-treated diabetic mice, INV-202-challenged mice displayed a marked decrease in many clinical features of DN such as albuminuria, albumin-to-creatinine ratio, urinary urea, loss of glomerular filtration rate and renal hypertrophy. Interestingly, we also found an improvement in both podocyte and proximal tubular cells morphology and health markers that were likely responsible for the improvement previously mentioned. In addition, INV-202 led to a downregulation of the angiotensin II receptor expression as well as a reduced urinary excretion, suggesting an inhibitory effect of this compound on the angiotensin II-mediated renal dysfunction in the context of DN. Furthermore, INV-202 also led to a drastic reduction in renal inflammation and oxidative stress markers that are known to be highly involved in the pathogenesis of DN. Finally, despite the limitation of our model in regard to interstitial fibrosis development, we could observe a marked anti-fibrotic effect of INV-202. CONCLUSION: Treatment with INV-202 reduced the progression of nephropathy in STZ-induced diabetic mice. Improvements in kidney size, function and histology, with corresponding gene expression, were noted with both doses of INV-202. Further work to explore the effect of INV-202 in humans is warranted.